2021
DOI: 10.1007/s00354-021-00128-0
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Artificial Intelligence (AI) Capabilities for COVID-19 Containment

Abstract: The Coronavirus disease (COVID-19) is an infectious disease caused by the newly discovered Severe Acute Respiratory Syndrome Coronavirus two (SARS-CoV-2). Most of the people do not have the acquired immunity to fight this virus. There is no specific treatment or medicine to cure the disease. The effects of this disease appear to vary from individual to individual, right from mild cough, fever to respiratory disease. It also leads to mortality in many people. As the virus has a very rapid transmission rate, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 58 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…We present the role of AI in seven different ECS that were extensively used in COVID-19 in Figure 5. Based on the extensive review of published studies, we found that AI remained a critical component of every ECS developed to contain the spread of COVID-19 [33][34][35][36][37]. Apart from the services cited in Figure 5, AI can play a vital role in alerting people stay away from the virus contaminated places pro-actively.…”
Section: Perspective 1: Epidemic Containment Strategies and Ai Rolementioning
confidence: 99%
“…We present the role of AI in seven different ECS that were extensively used in COVID-19 in Figure 5. Based on the extensive review of published studies, we found that AI remained a critical component of every ECS developed to contain the spread of COVID-19 [33][34][35][36][37]. Apart from the services cited in Figure 5, AI can play a vital role in alerting people stay away from the virus contaminated places pro-actively.…”
Section: Perspective 1: Epidemic Containment Strategies and Ai Rolementioning
confidence: 99%
“…One paper applies fuzzy technologies [ 1 ]. Another introduces the AI technologies for COVID-19 containment [ 2 ]. Another publication proposes computer-aided-diagnosis as a service on decentralized medical cloud for efficient and rapid emergency response intelligence [ 3 ].…”
Section: Selected Papersmentioning
confidence: 99%
“…The unique potential of this field is that it can analyze massive amounts of data quickly without human intervention. For example, during the time of the COVID-19 pandemic, an unprecedented number of individuals were infected, and AI-based systems were programmed to automatically detect the presence of COVID-19 in individuals [ 3 , 4 ]. Additionally, the performance of AI-assisted CT scan imagery analysis is equivalent to an expert radiologist [ 5 ].…”
Section: Introductionmentioning
confidence: 99%